Excursia ca modalitate de învățare experiențială în educația elevilor cu cerințe educaționale speciale [Articol] - Moroșan, Elena Mihaela (Editura USM, 2024)
The excursion is a teaching tool of great importance in relation to the cognitive and affective development of students with CES, giving students the opportunity to observe, research, orient themselves and know directly a wide variety of aspects of the environment. The excursion as a teaching method ensures the acquisition of knowledge, through the direct perception of the objectives and phenomena realizing the dialectical path of knowledge: in the excursions, students with CES acquire new knowledge, study the phenomena and objects in all their complexity, clarify and fix the acquired knowledge better in the classroom, by linking theory to practice; in excursions, skills and abilities to observe the phenomena of nature and social-economic life are formed and, through direct intuition, knowledge acquires a realistic character, revealing their causal links, excursions are a rich source of enrichment of geographical thinking and application of knowledge acquired during the course hours. The student can deepen certain learning contents in the field of physical or economic geography.
Keywords: trip; student with CES; experiential learning; cognitiv development; elevi cu CES